Social work law, ethics and policy - Sabbagh, Muna; Korgaonkar, Gill (SAGE, 2022)
"Understanding the law is a core part of your degree course, and an essential part of being a social worker in practice. You need to know the relevant areas of law, the legal processes, and how they relate to social work in practice, so that you are equipped with the knowledge and skills to fulfil your responsibilities to your client(/service user). This book covers all the areas of law you need to know: social work with children and families, vulnerable adults and social issues such as welfare and homelessness. Each section concludes with a discussion of how social policy and ethics relate to each area of social work law. This gives real-world context to what you have learnt, alongside thought boxes, exercises and case studies in each chapter to further encourage reflection and put theory into practice"--